Pengaruh Kebijakan Peningkatan Upah Minimum terhadap Ketimpangan Upah (Studi Kasus Provinsi-Provinsi di Jawa) - Rohmah, Zaitun; Sastiono, Prani (UI Scholars Hub, 2021)
This research estimates the effect of the minimum wage increase on the wage inequality in Java provinces between 2008 and 2014 using semiparametric methods. It is found that the increase in minimum wage decrease the wage inequality in DKI Jakarta, West Java, Central Java, and Banten Provinces if the employment effects of the minimum wage increase are ignored and the opposite results if we consider the employment effects. Different results occur in Yogyakarta Special Region and East Java provinces, the minimum wage increase will lead to an increase in wage inequality both for the inclusion or exclusion of the employment effects.